Hyperekplexia in a neonate: a seizure mimicker - Agarwalla, Sunil Kumar; Patro, Debasis; Ali, Nasreen; Pattanaik, Ankita (International Journal of Research in Medical Sciences, 2017)
Hyperekplexia is an exaggerated startle to external stimuli associated with generalized increase in tone seen in a normal newborn with both sporadic as well as genetic predisposition. This is an uncommon neurological entity that is often confused with seizure in infancy. To date about 150 cases have been reported in the literature. We report a 6-week-old infant with characteristic intermittent generalized tonic spasm misdiagnosed as seizure disorder and was on phenobarbitone. With characteristic stiffening episode and exaggerated startle without habituation on tapping the nose we came to a clinical diagnosis of Hyperekplexia or Stiff baby syndrome or Startle disease. The child was started on Clonazepam to which he responded remarkably with decreased startle reflex. The aim of this case reporting is to through insight to this disease entity when we see an intermittent hypertonic infant.